Drought Risk Assessment In Iraq Using Remote Sensing And GISTechniques - AL-Timimi, Yaseen; George, Loay; AL-Jiboori, Monim (Iraqi Journal of Science, 2024)
This paper aims to investigate the drought levels in Iraq using Remote Sensing andGIS Techniques. Meteorological and Agricultural droughts were calculated based onStandardized Precipitation Index (SPI) and Anomaly of Normalized DifferenceVegetation Index (NDVI), respectively. The drought risk maps were prepared bycalculating the classes frequency of droughts. Finally, a resultant risk map wasobtained by integrating agriculture and meteorological drought risk maps. Theresults indicated that 14.4% area has Slight drought, 61.6% area face moderate risk,23.2% area face severe risk and 0.8% area face very severe risk within the studyarea. It was evident from the study that northwest of Iraq is more prone to drought.